Late vitamin K deficiency bleeding in an infant with choledochal cyst - Krstovski, Nada; Janic, Dragana; Dokmanovic, Lidija; Lazic, Jelena; Rodic, Predrag; Krstic, Zoran (The Turkish Journal of Pediatrics, 2010)
Infantile choledochal cyst (CC) usually presents as jaundice, vomiting, acholic stools, and hepatomegaly, and it can resemble biliary atresia. Although bleeding tendency is a rare clinical presentation of CC, it can be the first symptom, especially in infants less than 12 months of age. We report a case of a two-month-old infant with choledochal cyst presenting as late vitamin K deficiency bleeding (VKDB). Early recognition of diseases predisposing to VKDB and immediate investigation and treatment of warning bleeds help to prevent the worst consequences. Late VKDB is often the presenting feature of a serious underlying disease that may be recognized early. The sudden onset of bleeding tendency in infants with congenital liver or biliary tract disease may suggest not only biliary atresia but also, although extremely rare, CC. Early vitamin K administration leads to rapid normalization of hemostatic parameters, which enables major liver surgery.